An analysis of the reinsurance market - Stloukalová, Aneta (2015)
The main topic of this bachelor thesis is an analysis of the reinsurance market. Firstly, the thesis is focused on introduction of reinsurance, its development, its forms and also on the reinsurance market players. The thesis introduces not only the traditional forms of risk transfer, but also the alternative ones, which had significant influence on the development of the reinsurance market. Then it characterises current trends and changes on the reinsurance market and, based on that, it provides prognosis of future development of the market. The last part is dedicated to the reinsurance market in the Czech Republic and to the first Czech reinsurance company VIG Re.